2012
DOI: 10.1128/aem.05938-11
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Bartonella Species in Wild Carnivores of Northern Spain

Abstract: The genus Bartonella was detected by PCR in 5.7% (12/212) of wild carnivores from Northern Spain. Based on hybridization and sequence analyses, Bartonella henselae was identified in a wildcat (Felis silvestris), Bartonella rochalimae in a red fox (Vulpes vulpes) and in a wolf (Canis lupus), and Bartonella sp. in badgers (Meles meles).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 24 publications
3
32
1
3
Order By: Relevance
“…Several studies have reported detection or isolation of Bartonella species in coyotes (Canis latrans), raccoons (Procyon lotor), gray foxes (Urocyon cinereoargenteus), island foxes (Urocyon littoralis), and other wildlife from multiple regions across the world, including the western US (Chang et al 2000;Gerrikagoitia et al 2012). Two Bartonella species, B. vinsonii subsp.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported detection or isolation of Bartonella species in coyotes (Canis latrans), raccoons (Procyon lotor), gray foxes (Urocyon cinereoargenteus), island foxes (Urocyon littoralis), and other wildlife from multiple regions across the world, including the western US (Chang et al 2000;Gerrikagoitia et al 2012). Two Bartonella species, B. vinsonii subsp.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 22 genotypes of Bartonella were detected in small mammals (29), some of them corresponding to a potentially new Bartonella species. In wild carnivores, B. rochalimae was detected in a wolf and in a fox (30). A potential new Bartonella species, closely related to B. clarridgeiae, was found in badgers (30).…”
mentioning
confidence: 97%
“…In wild carnivores, B. rochalimae was detected in a wolf and in a fox (30). A potential new Bartonella species, closely related to B. clarridgeiae, was found in badgers (30). Currently, data about the Bartonella species which are circulating in domestic ungulates in this region of Spain are scarce.…”
mentioning
confidence: 99%
“…However, as in this study, A. phagocytophilum was not detected in badgers in The Netherlands, Czech Republic, and Spain and only a low prevalence was observed among badgers in another study conducted in Belgium and The Netherlands, as well as in Italy, suggesting badgers do not play a significant epidemiological role in this infection ( [32] and references therein). A previous survey found what appeared to be a novel Bartonella sp., most closely related to B. clarridgeiae, in 12% of badgers in northern Spain [38]. B. clarridgeiae infection is largely associated with cats and dogs, and more recently humans [39], so further investigation of a larger number of badgers would be interesting.…”
Section: Discussionmentioning
confidence: 99%